Come la consulenza direzionale crea conoscenza Prospettive di convergenza tra scienza e consulenza - Ciampi, Francesco (Studi e saggi, 2017)
The management consulting firm is commonly considered the archetype of the knowledge-intensive firm. However, the theme of knowledge creation through the implementation of the consultancy intervention is still a widely unexplored research field . This work aims at filling this gap by proposing a conceptual model whose aim is to clarify and trace the cognitive paths used as a means of expression by the potential of managerial knowledge creation of the management consultancy intervention. The proposed model represents originally applies the theories interpreting the dynamics of knowledge creation as knowledge conversion processes to the specific context of the consultancy relationship. It contributed to the understanding that, in advanced consultancy contexts, this potential consists in the possibility of generating new entrepreneurial knowledge which is not only explicit but also, and above all, silent (such as, for example, new experiential diagnostic skills and new abilities for the intuition of the solution to business problems).